1391 Occupational lung diseases in deceased south african women in mining. (24th April 2018) - Ndlovu, Ntombizodwa; Phillips, Jim; Kgokong, Ntebogeng; Vorster, Trudie; Murray, Jill
Abstract : Introduction: Women have worked in South African mines for over a century. During the twentieth century, employment of women underground was legally prohibited. In the asbestos mining industry, women worked in surface processing activities e.g. hand-cobbing of asbestos. Most women were undocumented in mine employment records and were thereby excluded from medical surveillance and compensation. Women continue to be exposed to asbestos in the environment. The 2004 Mining Charter permitted women to work underground and set targets to their employment across the mining industry. From 2005, the National Institute for Occupational Health (NIOH) has recorded the sex of deceased individuals examined for the detection of OLDs for statutory compensation. We compared OLDs in deceased women and men. Methods: Records were extracted from the PATHAUT autopsy database (2005–2015). The NIOH also performs autopsies for the Asbestos and Kgalagadi Relief Trusts that compensate qualifying miners and environmental claimants. Results: Women comprised 2.47% (n=394) of 15 940 cases. The women were older (56.6±17.11 years) than men (53.63±14.44 years) and had shorter mining-related exposures (7.21±7.71 versus 18.18±18.20 years). Most women had asbestos mining (46.19%) or environmental (14.72%) exposure; 87 (22.08%) were gold and 37 were platinum (9.39%) miners. Among men, there were 64.28% gold, 18.47% platinum and 5.55% asbestos miners, and 0.30% had environmental asbestos exposure. Disease proportions in women and men were: emphysema, 16.00% and 27.73%; silicosis, 3.30% and 23.13%; tuberculosis, 17.77% and 23.13%; lung cancer, 4.31% and 3.67%; asbestosis, 16.75% and 4.28% and mesothelioma, 17.26% and 2.00%. Discussion: The burden of asbestos-related diseases was high in women. The few cases of silicosis in women are an alert to high silica dust exposures. The study highlights the importance of autopsies for disease diagnosis, and education of women on mining and environmental OLD-related risks and their right to access statutory compensation.